2021
DOI: 10.1055/s-0041-1740978
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health of Siblings of Children with Rare Congenital Surgical Diseases during the COVID-19 Pandemic

Abstract: Introduction The COVID-19 pandemic has affected every aspect of our society, particularly vulnerable groups, such as families with children suffering from rare diseases. However, the psychosocial influences of COVID-19 on the healthy siblings of children with rare diseases have not been investigated yet. Thus, the study aimed to evaluate the mental health of healthy siblings of children with rare congenital surgical diseases during the COVID-19 pandemic. Material and methods Siblings of children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…An exception is social aspects, in which our study population also differs significantly from the control group. A previous study has shown that contact with hospitals in childhood is fundamentally associated with a high level of stress for the entire family and leads to decreased HRQoL and mental health [38]. This could explain our results, considering that our control group was not fully healthy at the time of the survey but also received surgery.…”
Section: Discussionmentioning
confidence: 75%
“…An exception is social aspects, in which our study population also differs significantly from the control group. A previous study has shown that contact with hospitals in childhood is fundamentally associated with a high level of stress for the entire family and leads to decreased HRQoL and mental health [38]. This could explain our results, considering that our control group was not fully healthy at the time of the survey but also received surgery.…”
Section: Discussionmentioning
confidence: 75%
“…The geographical distribution of data in the studied material showed a prevalence of research in continental Europe, with 61.1% of the total yield of studies coming from this region. Of these ten documents, five were from England [9,10,14,23,24], three were from Italy [5,7,11], two were from Germany [8,25], and one was from Norway [13]. After Europe, two articles were from North America [12,18], one was from Asia (Hong Kong) [26], one was from the Asia-Pacific region [17] (based on data from Australia, Hong Kong, India, Japan, China, Malaysia, New Zealand, the Philippines, Singapore, and Taiwan), one was from South America (Brazil) [6], and, finally, there was one that took a broad global perspective [19].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding RDs, nine documents approached the theme in a broad, general way [6,8,[12][13][14]17,19,25,26], while the rest focused on one or two diseases or on a specific group of diseases per publication. The RDs mentioned in the articles were hereditary haemorrhagic telangiectasia (HTT) [5], lysosomal storage disorder (LSD) [7], Batten disease [18], interstitial cystitis/bladder pain syndrome (IC/BPS) [11], osteogenesis imperfecta [10], congenital surgical diseases [25], oesophageal atresia/tracheo-oesophageal fistula (OA/TOF) [9], rare neurogenetic conditions [24], and macrocytosis [23].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations